Attosecond spatial interferometry for complete three-dimensional electric field reconstruction - Carpeggiani, P. A.; Reduzzi, M.; Comby, A.; Ahmadi, H.; Ku¨hn, S.; Calegari, F.; Nisoli, M.; Frassetto, F.; Poletto, L.; Hoff, D.; Ullrich, J.; Schro¨ter, C. D.; et al. (Optics InfoBase Conference Papers, 2018)
We demonstrate the complete temporal reconstruction of visible pulses with a time-dependent polarisation state, using extreme ultraviolet spatial interferometry based on two coherent isolated attosecond pulses.
CRIS-Team Scopus Importer:2023-04-20